Implementation Of Public Housing Management Policy: A Case Study In Rusunawa Of Cimahi, West Java, Indonesia - Deden Hadi Kushendar (Jurnal Manajemen Pelayanan Publik, 2023)
Insufficient and affordable vertical housing (rusunawa) availability is still emerging as an alternative option for temporary residence for low-income individuals. Therefore, this study purposes to explore the implementation of Rusunawa management policies managed by local governments in Indonesia. The theoretical framework used to analyze policy implementation is based on Kearns and Lawson's (2008) concept, which examines four factors: 1) the policy itself, 2) implementing agencies, 3) inter-organizational relations, and 4) social and political factors. This research adopts a qualitative case study approach, focusing on three Rusunawa (vertical housing) facilities managed by the Cimahi Government. The data were collected within interviews with 18 respondents using purposeful sampling, employing open-ended questions complemented by observation and analysis of relevant documents. The implications of this research highlight the requirement for public rental housing management policies to consider the income criteria of prospective residents, rental period duration, and budget allocation for expanding the Rusunawa Public Service Unit (PSU), effective communication and information dissemination channels, and improved Rusunawa management practices. The findings underscore the socio-economic factors influencing the beneficiaries of general rental housing policies, along with the budgetary requirements for expanding the Rusunawa PSU, optimizing communication and information channels, and enhancing the overall management of Rusunawa facilities.